Preferences of women for maternal healthcare services in low-income and middle-income countries: a systematic review of discrete choice experiments - Richard Norman; Daniel Gashaneh Belay; Bereket Kefale; Melaku Birhanu Alemu; Jennifer Dunne; Gizachew A. Tessema (BMJ Global Health)
Background Maternal healthcare service utilisation during pregnancy, childbirth and the subsequent postpartum periods could improve the health outcomes of women and newborns. However, women in low-income and middle-income countries (LMICs) have a lower uptake of these services, which is partly attributed to a lack of access to preferred maternal health services. This study systematically synthesised evidence on women’s preferences for maternal healthcare services in LMICs.Methods A systematic search was undertaken from PubMed/MEDLINE, EMBASE, PsycINFO, CINAHL, Scopus and Global Health databases, and supplemented with Google Scholar for grey literature. We have included published articles from 1 January 2000 to the date of the last search, 14 July 2023. Studies were included if they reported preferences of women for maternal health services in LMICs using the stated preference analysis methods. The quality of the included papers was assessed using the conjoint analysis applications in the healthcare checklist. We have thematically presented the attributes using a healthcare access framework (accessibility, availability, accommodation, affordability and acceptability). The first two most important and least important attributes in each study were identified based on the relative importance scores.Findings Of the 54 articles identified for full-text review, 15 studies from eight LMICs met the inclusion criteria for the final review. Attributes related to the acceptability of healthcare services, such as a provider’s good attitude and rapport (47.1%), and the availability of services, such as medications and supplies (41.2%), were typically considered the most important by women. Conversely, accessibility attributes, such as increased distance or travel time to health facilities (29.4%), and affordability attributes, such as increased cost of services (23.5%), were generally less valued by women.Interpretations The acceptability and availability attributes of healthcare services were considered the most important by women. Aligning maternal healthcare service provision with women’s preferences can promote person-centred care, leading to increased service uptake.PROSPERO registration number CRD42023444415.